2022
DOI: 10.3390/ijerph19159015
|View full text |Cite
|
Sign up to set email alerts
|

Differences and Influencing Factors of Relative Poverty of Urban and Rural Residents in China Based on the Survey of 31 Provinces and Cities

Abstract: China achieved comprehensive poverty eradication under the current standards in 2020, but eliminating absolute poverty does not mean the end of poverty alleviation and reduction; relative poverty will exist for a long time and has become the subject of poverty study. In this paper, the social poverty line (SPL) index is utilized to establish the relative poverty standard, and CHFS2017 is used to compare the regional distribution of relative poverty in China. The results show that the relative poverty in rural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 37 publications
0
20
0
1
Order By: Relevance
“…Scholars have explored this area to some extent, including but not limited to the connotation of relative poverty [6,7], the motivations for migration and the impact of migration on poverty [8,9]. In rural areas, some individuals migrate to other areas in search of resources to improve their economic level and status.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have explored this area to some extent, including but not limited to the connotation of relative poverty [6,7], the motivations for migration and the impact of migration on poverty [8,9]. In rural areas, some individuals migrate to other areas in search of resources to improve their economic level and status.…”
Section: Introductionmentioning
confidence: 99%
“…The urban relative poverty rate in many provinces and cities of the central and western regions is about 40% ( 56 ). Relative poverty has been shown to have an adverse effect on children's social-emotional development, and research has indicated that the adverse effect of relative poverty is bigger when children are older ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…The urban relative poverty rate in many provinces and cities of the central and western regions is about 40% (56). Relative poverty has been shown to have an adverse effect on children's Boot standard error, BootCL lower limit and BootCL upper limit refer to the standard error of the indirect effect estimated by the bias-corrected percentile bootstrap method (5,000 times), the lower limit and the upper limit of the 95% confidence interval, respectively.…”
Section: The Mediating Role Of Positive Academic Emotions and Conduct...mentioning
confidence: 99%
“…3) Kemiskinan relatif (relative poverty) umumnya ditemukan untuk rumah tangga dengan pendapatan di bawah proporsi rata-rata pendapatan nasional Pertumbuhan ekonomi merupakan adalah indikator keberhasilan pembangunan di suatu perekonomian. Kesejahteraan dan kemajuan suatu perekonomian ditentukan oleh besarnya pertumbuhan yang ditunjukkan oleh perubahan output nasional (Sun et al, 2022). Pertumbuhan ekonomi sejatinya merupakan proses yang berujung pada peningkatan kemakmuran rakyat, salah satunya adalah pengurangan angka kemiskinan (Afandi1 & Dwi Wahyuni2, 2017).…”
Section: Pendahuluanunclassified